Analisis Epidemiologi Prevalensi dan Faktor Risiko Hipertensi Berdasarkan Variabel Orang, Tempat, dan Waktu di Kota Palembang - Intan Kumalasari (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Hypertension is one of the leading non-communicable diseases and remains a major public health concern in Indonesia, particularly in urban areas such as Palembang. The rising prevalence of hypertension is influenced by several risk factors, including age, gender, family history, unhealthy lifestyle, and environmental conditions. This disease significantly contributes to morbidity and mortality rates, thus requiring a targeted and continuous surveillance strategy. This study aims to analyze the distribution of hypertension prevalence and its risk factors based on person, place, and time variables. Secondary data were obtained from hypertension screening at Multiwahana Public Health Center in Palembang in 2024. A descriptive quantitative method with frequency analysis was applied to a sample of 411 hypertension patients. The results showed the highest prevalence among females aged over 60 years, with the highest concentration of cases found in Sialang Subdistrict, where access to healthcare services is better. The trend of cases fluctuated, peaking in March 2024. These findings provide an important epidemiological overview to support preventive and promotive health policies at the primary care level.